Assessment of ecological asset quality and its drivers in Agro-pastoral Ecotone of China - Wenmin Liu; Zhiyuan Cheng; Jie Li; Guang Li; Ninghui Pan (Ecological Indicators)
Evaluation of ecological asset quality is a prerequisite for resource management and ecological protection, and objective, timely, and quantitative assessment of ecological asset quality is of great significance for ecological construction and sustainable development strategies. In this study, we synthesized soil, topography, and perpendicular indicators, based on Sen + MK trend analysis, Hurst index analysis, and Pearson correlation analysis methods, combined with climate and socio-economic data, and took the municipal scale of Agro-pastoral Ecotone of China as the study unit to quantitatively assess the spatial and temporal changes of ecological asset quality in the study area from 2000 to 2020, and to identify the influencing factors that generate spatial heterogeneity. The results show that: (1) The overall ecological asset quality of the zone was between 0.35 and 0.5 from 2000 to 2020, which was located at a medium grade and accounted for 47.08 % of the total area. The spatial heterogeneity was obvious, showing a distribution pattern of high in the northeast-southwest and low in the middle, and it was mainly concentrated in the high-elevation zone of 2968–6702 m and the low-elevation zone of −3–785 m. The distribution pattern of the ecological assets was also obvious, showing a distribution pattern of high in the northeast and low in the middle. (2) The effects of altitude and latitude/longitude on the quality of ecological assets in the study area were mainly characterized by a decreasing trend in the quality of ecological assets with decreasing altitude from west to east, and a decreasing and then increasing trend in the quality of ecological assets with increasing altitude from south to north. (3) The quality of ecological assets has a complex correlation with climate and socio-economic factors, among which, temperature and precipitation are significantly positively correlated in the middle altitude (785–2968 m) and low altitude northwest; socio-economic factors are significantly positively correlated with large and medium-sized agricultural tractors, agricultural, forestry, animal husbandry and fishery population and rural population in the high altitude area, significantly positively correlated with GDP of the primary industry in the middle altitude area, and significantly positively correlated with agricultural population and animal husbandry and fishery population in the low altitude area. (4) The construction of a comprehensive assessment system that introduces soil and terrain indices mainly shows an increase in the proportion of medium and low grades of ecological asset quality and a decrease in the proportion of excellent, good, and poor grades, compared with the quality of ecological assets using only the perpendicular index as the assessment system. This study reveals the relationship between the spatial distribution characteristics of ecological asset quality and climatic-socio-economic factors in Agro-pastoral Ecotone of China and further reflects the quality of regional ecological assets objectively by introducing more comprehensive assessment indicators. The results of the study not only provide a scientific basis for the effective monitoring and improvement of the quality of regional ecological assets, but also provide theoretical support for the formulation of relevant ecological environmental protection policies, as well as data support and decision-making reference for future ecological management and sustainable development strategies.